2011
DOI: 10.1021/jp206881t
|View full text |Cite
|
Sign up to set email alerts
|

Change from Glyme Solutions to Quasi-ionic Liquids for Binary Mixtures Consisting of Lithium Bis(trifluoromethanesulfonyl)amide and Glymes

Abstract: Lithium ion batteries (LIBs), with high energy and power densities, have become essential to modern society as power sources for portable electronic devices. 1À3 Furthermore, electric vehicles (EVs) equipped with LIBs are now commercialized. The conventional electrolyte of LIBs is composed of mixed organic solvents (cyclic carbonate and linear carbonate) and LiPF 6 . 4 Linear carbonate solvents are extremely flammable, with flash points below room temperature, and LiPF 6 decomposes into HF with the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
246
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 192 publications
(276 citation statements)
references
References 63 publications
28
246
2
Order By: Relevance
“…18 To optimize the solvate ionic liquids for battery application, it is needed to investigate the properties of the LiTFSA-glyme solvate ionic liquids with a wide composition range. Although the properties of the solvate ionic liquids at X LiTFSA5 0 mol% have been reported so far, 13 those at X LiTFSA > 50 mol% have not been studied yet. In the present study, such fundamental transport properties as the viscosity and ionic conductivity of the LiTFSA-glyme solvate ionic liquids at X LiTFSA from 50.0 to 54.5 mol% were investigated in the temperature range from 298 to 323 K.…”
Section: à ð1þmentioning
confidence: 99%
See 1 more Smart Citation
“…18 To optimize the solvate ionic liquids for battery application, it is needed to investigate the properties of the LiTFSA-glyme solvate ionic liquids with a wide composition range. Although the properties of the solvate ionic liquids at X LiTFSA5 0 mol% have been reported so far, 13 those at X LiTFSA > 50 mol% have not been studied yet. In the present study, such fundamental transport properties as the viscosity and ionic conductivity of the LiTFSA-glyme solvate ionic liquids at X LiTFSA from 50.0 to 54.5 mol% were investigated in the temperature range from 298 to 323 K.…”
Section: à ð1þmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Some lithium salts are able to be dissolved in glymes (Gn, CH 3 O(CH 2 CH 2 O) n CH 3 ), such as triglyme (G3, n = 3) and tetraglyme (G4, n = 4), at extremely high concentrations (> 3 mol dm ¹3 ). 13,14 It has been known that stoichiometric LiTFSAglyme mixtures (TFSA ¹ = bis(trifluoromethylsulfonyl)amide), of which the mole fractions of LiTFSA, X LiTFSA , are 50 mol%, are able to be regarded as solvate ionic liquids since the mixtures consist of a complex cation of lithium ion and glyme, [Li(glyme)] + , and TFSA ¹ anion according to the following equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…[89][90][91][92] We explored a variety of such combinations and found that, in certain combinations, these materials have similar properties to conventional aprotic ILs. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] We conclude that these mixtures can be categorized as "solvate ILs," i.e., liquids consisting of a salt and a solvent that strongly coordinates with cations or anions to form stable solvate ions. 110 Detailed studies of the solvate IL on the transport properties, [93][94][95][96][97][98][99] spectroscopic, [99][100][101][102][103] crystallographic, [100][101][102][103] electrochemical, [94][95][96]104,105 quantum mechanical characterizations, [106][107][108]…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 91%
“…19 The isothermal TG measurements revealed that the molten complexes did not show any weight loss that corresponded to the evaporation of the glymes at 100°C. 12 Additionally, the molten complexes are much less flammable than organic electrolytes (e.g., 1 20 and a lithium ionic liquid bearing oligoether-functionalized, fluoroalkyl borate anion 21 for comparison. The molar conductivity ratio ($ imp /$ NMR ) is also listed in Table 1 as an ionicity scale, and it can be determined from the experimental molar conductivity ($ imp ) and a predicted molar conductivity ($ NMR ) from the self-diffusion coefficients of the ions (D + and D ¹ ) on the basis of Nernst-Einstein equation for 1:1 molten salt:…”
Section: ¹1mentioning
confidence: 99%